Clathrin-mediated trafficking and PIN trafficking are required for auxin canalization and vascular tissue formation in Arabidopsis. (April 2020) - Mazur, Ewa; Gallei, Michelle; Adamowski, Maciek; Han, Huibin; Robert, Hélène S.; Friml, Jiří
Highlights: Auxin canalization mediates vasculature formation and regeneration in stem. Clathrin-mediated trafficking is required for auxin-conducting channels and vasculature formation. Actin cytoskeleton is crucial for auxin-conducting channels and vasculature formation. PIN trafficking mediates auxin-conducting channels and vasculature formation. Clathrin-mediated trafficking and actin-mediated PIN trafficking are involved in auxin canalization. Abstract: The flexible development of plants is characterized by a high capacity for post-embryonic organ formation and tissue regeneration, processes, which require tightly regulated intercellular communication and coordinated tissue (re-)polarization. The phytohormone auxin, the main driver for these processes, is able to establish polarized auxin transport channels, which are characterized by the expression and polar, subcellular localization of the PIN1 auxin transport proteins. These channels are demarcating the position of future vascular strands necessary for organ formation and tissue regeneration. Major progress has been made in the last years to understand how PINs can change their polarity in different contexts and thus guide auxin flow through the plant. However, it still remains elusive how auxin mediates the establishment of auxin conducting channels and the formation of vascular tissue and which cellular processes are involved. By the means of sophisticated regeneration experiments combined with local auxin applications in Arabidopsis thaliana inflorescence stems we show that (i) PIN subcellular dynamics, (ii) PIN internalization by clathrin-mediated trafficking and (iii) an intact actin cytoskeleton required for post-endocytic trafficking are indispensable for auxin channel formation, de novo vascular formation and vascular regeneration after wounding. These observations provide novel insights into cellular mechanism of coordinated tissue polarization during auxin canalization.